2018
DOI: 10.1089/hs.2018.0026
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Healthcare Provider Use of Public Health and Other Information Sources by Provider Type and Practice Setting During New York City's Response to the Emerging Threat of Zika Virus Disease, 2016

Abstract: The New York City (NYC) Department of Health and Mental Hygiene (DOHMH) used multiple methods to provide guidance to healthcare providers on the management and prevention of Zika virus disease during 2016. To better understand providers' use of information sources related to emerging disease threats, this article describes reported use of information sources by NYC providers to stay informed about Zika, and patterns observed by provider type and practice setting. We sent an electronic survey to all email addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Studies have shown that health personnel in Zika endemic areas have a high level of awareness, but a low level of knowledge and preventive practices related to Zika virus prevention; especially as it relates to sexual transmission and prevention of sexual transmission . Our results similarly demonstrate that frontline healthcare personnel in Piura (nurses and midwives) generally know about Zika virus but have received uneven training.…”
Section: Discussionsupporting
confidence: 64%
“…Studies have shown that health personnel in Zika endemic areas have a high level of awareness, but a low level of knowledge and preventive practices related to Zika virus prevention; especially as it relates to sexual transmission and prevention of sexual transmission . Our results similarly demonstrate that frontline healthcare personnel in Piura (nurses and midwives) generally know about Zika virus but have received uneven training.…”
Section: Discussionsupporting
confidence: 64%
“…[37] Similarly, this was supported by other studies have shown that health personnel in ZIKА endemic areas have a low level of preventive practices related to ZIKА virus prevention. [76][77] Also, another study declared that insufficient participants practices in ZIKА prevention. [45] In the same line the results agreed with the finding showed all categories of healthcare providers showed а low level of knowledge and practices in pre-program as compared to post-program.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence access approaches included public or member-only repositories (e.g. websites, hubs, portals) [49,52,62], the use of rapid evidence response teams/services [46,72]; free/open access to journals [50,58,60] and communication mechanisms such as email lists and bulletins [40,42,49,56]. Learning resources (e.g.…”
Section: Pandemic Crisesmentioning
confidence: 99%
“…Practical barriers were associated with maintaining information systems for KE (e.g. platforms/databases) [32,34,40,47,56,60,64,65,76,86,93,102,103,109,112], a lack of IT/technical capability [32,71,84,107,110] and sensitivities with sharing data [52,76,102,103]. Barriers associated with delivering KE were also highlighted (e.g., insufficient reach of activities) [26,53,54,74,106,112], with several studies pointing to a lack of human and financial resources to support KE [34,47,53,54,[57][58][59]65,66,72,74,75,81,92,102,106].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation